WEBMAP UNTUK PENGEMBANGAN JALUR IRIGASI BARU DI KABUPATEN LAMONGAN - Ghozali, Imam; Riswandha Imawan, Moh; Rifqi Zamzami, Moh.; Zuhri, Saifuddin (Lafadz Jaya Publisher, 2024)
The problem of agricultural water, which frequently entails water shortages in various developing countries, has existed and gotten worse since the late 1980s, when the idea of global warming was first introduced. The existing system of archiving geographical data in Lamongan Regency is still organised as a manual for each district. Therefore, a new system is required that makes use of web-based information system technology to organise, analyse, and handle geographic data (spatial reference). If the Irrigation Public Works Agency (DPUP) needs to find suitable areas to build new irrigation canals, it can consult Webmap, a web-based geographic information system. There are previously established criteria, such as parameters, in the region to solve the associated difficulties. New irrigation canals in Lamongan District necessitate the creation of a Webmap, a tool for collecting, integrating, manipulating, analysing, and displaying information about the location and state of land. This capstone project details the development and launch of a Webmap. Considering the regularity with which information is updated, this strategy can stand in for conventional data warehouses.